(untitled) (Reabilitacijos mokslai: slauga, kineziterapija, ergoterapija, 2010)
The subject of the research: The effect of dance and movement therapy.The problem of the research: Years are going on and old people meet a problem that their gait changes, their balance becomes worse and the muscle power decreases. People who have cognitive impairment frequently demonstrate disturbed gait which put them into an increased risk to fall down and get injured seriously. Patients who are sick with dementia very often experience symptoms of depression the treatment of which is investigated insufficiently. It is known that dance and movement therapy positively impacts the health of the people with dementia, improves their emotions and mental conditions. Many foreign scientists investigate how dance and movement therapy affects old people’s balance, depression, but the following indexes of people who are sick with dementia are not researched. In Lithuania no pharmacological treatment of dementia is popular. Nowadays in our country there is no research about the effect of dance and movement therapy’s effect on people who are sick with dementia, how it impacts their depression and static and dynamic balance. The hypothesis of the research: Dance and movement therapy can improve static and dynamic balance and reduce depression of the elderly who are sick with dementia The aim of the research was to evaluate the effect of dance and movement therapy on balance and depression of the elderly who are sick with dementia: The goals of the research were: To establish the effect of dance and movement therapy to static and dynamic balance for old people sick with dementia. To establish the effect of dance and movement therapy for depression of old people sick with dementia. Several conclusions were made in on the basis of the results of this study: Dance and movement therapy can help improve static and dynamic balance for the elderly with dementia (p < 0. 05). Dance and movement therapy can help reduce depression of the elderly with dementia (p < 0.05). Keywords: dementia, balance, depression, dance and movement therapy.